ANALISIS STRATEGI BAURAN PROMOSI PADA PERUSAHAAN MOCHI SEBAGAI USAHA MAKANAN KHAS DAERAH DI MASA PANDEMI COVID-19 - Ichlasul Amal Ramdhani Zein, - (2022)
As a result of the COVID-19 pandemic which lasted for more than a year, economic activity weakened. The tourism industry is one of the industries affected by the spread of this virus, it has a direct impact on related industries, one of which is the food and beverage industry. As with regional specialty food businesses, this study examines regional specialties food promotion strategies as a way to survive during the pandemic, with a case study at a mochi company located in the Kaswari mochi center, namely Mochi Kaswari Lampion and Mochi Kaswari Bakat Jaya. The purpose of this study is to explore what are the impacts of COVID-19, analyze the promotion mix strategy used by the company, and explore the challenges and obstacles in carrying out the strategy. The research method used is a case study method and the approach used is a qualitative approach. The results of this study indicate that there is an impact felt by regional culinary businesses due to the COVID-19 pandemic such as drastic declines in sales, price fluctuations and difficulty in mobilizing, while the company is digitizing the marketing and promotional strategy activities carried out, as well as finding various challenges and challenges. obstacles such as delays in the distribution of raw materials, shipping factors, human resource problems and also the last one regarding public policy.